Students as key allies in combating school bullying: Leveraging peer perspectives to recognize victimization in high-risk groups - Sung, Cheng-Hao (Journal of interpersonal violence, 2026)
Bullying in schools remains a critical issue, and teachers often struggle to identify students at risk of victimization. This study explores the prevalence of various forms of bullying among high-risk groups in Taiwanese schools, using peer perspectives to gain insight. A total of 1,732 students (734 males and 998 females) participated in a survey that measured 10 common types of bullying, assessing both students’ perceptions and the actual frequency of occurrences over the past 6 months. The multidimensional Rasch model (Kelderman, 1996) was employed to analyze the alignment between students’ perceptions of bullying and their actual experiences in school. The study produced three key findings: (a) Students with “personality or behavioral problems” were most likely to be bullied, followed by those with “abnormal appearance” and “hygiene problems.” (b) Peer reports on bullying behavior were generally accurate in identifying victims. (c) In assessing bullying related to “sexual orientation or gender identity,” there was a discrepancy between perceived peer views and the actual frequency of such bullying. These findings suggest that students can be crucial in combating school bullying. Stakeholders involved in prevention efforts should focus on students with personality or behavioral problems, as they are particularly vulnerable to victimization, which can perpetuate the cycle of bullying. In addition, schools should incorporate peer feedback to enhance their strategies for identifying and preventing bullying.